2018
DOI: 10.1186/s13104-018-3541-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of miRNA profile in human dendritic cells infected with respiratory syncytial virus and human metapneumovirus

Abstract: ObjectiveHuman metapneumovirus (HMPV) and respiratory syncytial virus (RSV) are responsible for respiratory diseases, mostly in children. Despite the clinical and epidemiological similarities between these two pneumoviruses, they elicit different immune responses. This work aims to further our understanding of the differential immune response induced by these respiratory viruses by determining the changes of small non-coding RNAs (miRNAs), which regulate gene expression and are involved in numerous cellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…For example, Mn 2+ ion uptake in neuron cells exposed to MnCl2 was shown to trigger upregulation of miR-6087 and miR-7704 (He et al 2017). Hsa-miR-7704 has also been validated as a miRNA that is upregulated by more than 20-fold in virus-infected dendritic cells (Baños-Lara et al 2018). MiR-342-3p was observed to be downregulated in A549 cells exposed to chitosan conjugated gold nanoparticles (Choi et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Mn 2+ ion uptake in neuron cells exposed to MnCl2 was shown to trigger upregulation of miR-6087 and miR-7704 (He et al 2017). Hsa-miR-7704 has also been validated as a miRNA that is upregulated by more than 20-fold in virus-infected dendritic cells (Baños-Lara et al 2018). MiR-342-3p was observed to be downregulated in A549 cells exposed to chitosan conjugated gold nanoparticles (Choi et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, hMPV infection in DCs also induces the expression of several microRNAs (miRs) such as hsa-miR-182-5p and hsa-miR-4634. Although several microRNAs are believed to be known regulators of DC functions, including maturation, antigen presentation, and cytokine production, no link between the target genes of the hMPV-induced miRNAs and DC function has been found [120,121].…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…A recent study by Baños-Lara et al showed a differential miRNA pattern expression in Monocyte derived DCs (MoDCs) induced by hMPV- and hRSV-infection. Therein, they report that hMPV induces a higher expression of has-miR-185–5p, a miRNA that affects different genes such as FOXO1, PDCD4 and RECK, among others; but the effect in the dysregulation of these genes is not reported ( 89 ). On the other hand, hRSV induces the expression of miR-4448, that is associated with the Akt/mTOR pathway, inhibiting apoptosis and, as a consequence, increasing cell survivor ( 90 ).…”
Section: Tlrs and Their Effects Over The Immune Response Induced By Hmentioning
confidence: 99%